Arte e programação na linguagem Processing - Mello, Patricia Oakim Bandeira de (2015)
Since the 1960s, many artists have been experimenting with computer technology to create artwork. Different programming languages have also emerged since then with the goal of making programming easier for people with various backgrounds and interests, such as artists and children. Processing is one of these programming languages. It was created in 2001 at the Massachusetts Institute of Technology (MIT) with the objective of streamlining programming in the visual arts field. Processing was widely adopted as the programming language used for teaching programming to artists in several countries and it is also used for the final production of works of art. Besides, it was the inspiration for Arduino, a prototyping platform for physical computing that has become quite popular. Entitled Art and Programming in the Processing language, this research aims to investigate the following question: "What are the relationships between software, programming, and art in the Processing programming language? The research debates, from the Processing perspective, software in society and art, in addition to examining the role of the artist-‐programmer -‐ the artist who works directly with programming languages. It discusses still the learning of programming as part of computer and code literacy. The research methodology is based on a literature review and critical analysis, along with a case study of the Processing programming language. The research is complemented by the direct experience of the author and two interviews. This research presents cultural aspects of art made with Processing, encompassing from the context of programming languages that make the programming activity easier up to aspects of free software and hacker culture in the community of artists-‐programmers that use Processing